Political Instability and Economic Vulnerability - Mulder, Christian; Bussiere, Matthieu (Washington, D.C. : International Monetary Fund, 1999)
This paper analyzes and tests the influence of political instability on economic vulnerability in the context of the 1994 and 1997 crises episodes. It constructs four political variables that aim at quantifying political instability. The paper finds that for countries with weak economic fundamentals and low reserves, political instability has a strong impact on economic vulnerability. The estimation results suggest that including political variables in economic models does improve their power to explain and predict economic crises. The paper concludes that countries are more economically vulnerable during and especially following election periods, and when election results are less stable than at other times.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet